2022
DOI: 10.1007/s43441-022-00415-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Pharmacovigilance Systems in Developing Countries Using the WHO Pharmacovigilance Indicators

Abstract: Background In the context of the growth of pharmacovigilance (PV) among developing countries, this systematic review aims to synthesise current research evaluating developing countries’ PV systems’ performance. Methods EMBASE, MEDLINE, CINAHL Plus and Web of Science were searched for peer-reviewed studies published in English between 2012 and 2021. Reference lists of included studies were screened. Included studies were quality assessed using Hawker et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The description of 43 articles is presented in Table 1 . 11 - 15 , 18 - 20 , 26 - 60 The research design included literature review (n = 3), 28 , 32 , 49 expert interview (n = 1), 48 empirical analysis (n = 2), 43 , 52 comparative analysis (n = 7), 12 , 15 , 35 , 42 , 47 , 58 , 59 retrospective analysis (n = 2), 19 , 41 questionnaire (n = 10), 14 , 20 , 26 , 27 , 37 - 40 , 55 , 56 description analysis (n = 6), 11 , 13 , 33 , 36 , 45 , 60 and mixed methods (n = 12). 18 , 29 - 31 , 34 , 44 , 46 , 50 , 51 , 53 , 54 , 57…”
Section: Resultsmentioning
confidence: 99%
“…The description of 43 articles is presented in Table 1 . 11 - 15 , 18 - 20 , 26 - 60 The research design included literature review (n = 3), 28 , 32 , 49 expert interview (n = 1), 48 empirical analysis (n = 2), 43 , 52 comparative analysis (n = 7), 12 , 15 , 35 , 42 , 47 , 58 , 59 retrospective analysis (n = 2), 19 , 41 questionnaire (n = 10), 14 , 20 , 26 , 27 , 37 - 40 , 55 , 56 description analysis (n = 6), 11 , 13 , 33 , 36 , 45 , 60 and mixed methods (n = 12). 18 , 29 - 31 , 34 , 44 , 46 , 50 , 51 , 53 , 54 , 57…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have found similar trends, with the majority of HCPs failing to report any ADR despite encountering it during their practice [ 15 , 17 , 37 , 47 ]. The rate of ADR reporting by various HCPs is very low in many countries [ 18 , 32 , 48 , 49 ] including Türkiye [ 20 – 22 , 50 ]. Our finding revealed that a higher proportion of pharmacists (55%) reported ADRs as compared to other HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacovigilance is crucial for drug safety and public health, particularly in emerging economies like China, where healthcare transformations necessitate improved pharmacovigilance knowledge, attitudes, and practices (KAP) among healthcare professionals and the public ( 1 , 2 ). As the global pharmaceutical market evolves, countries are enhancing their pharmacovigilance systems to meet international safety standards and regulatory benchmarks, such as the Good Regulatory Practices (GRP) introduced by the World Health Organization in 2021, aiming to standardize drug safety measures worldwide ( 3 , 4 ). This effort underscores pharmacovigilance’s key role in ensuring drug safety, reflecting a global consensus on the need for stringent regulatory frameworks.…”
Section: Introductionmentioning
confidence: 99%